(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
The article reports results from research study on gender differences in experience and expression of four primary emotions: anger, fear, joy and sadness, and motives for their regulation, in situations when object and person (target) to whom emotion expression is addressed are the same or different and when a present person is of the same or opposite sex. The research was conducted on a sample of 628 high school and university students, including 259 males and 369 females. The average age of participants is 17.9 years. Generally, the results indicate that female participants experienced almost all four emotions more intensely than males, regardless of the conditions in which they were, and irrespective of the sex of the person who was present at the moment. For all participants, the most frequent motive for regulation of emotional responses was the motive for improvement of own emotional state followed by cathartic effects.